2023
DOI: 10.1371/journal.pone.0289133
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet ameliorates attention deficit hyperactivity disorder in rats via regulating gut microbiota

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common mental behavioral disorder in children. Alterations in gut microbiota composition are associated with neurological disorders. We aimed to investigate whether a ketogenic diet (KD) can be an alternative therapy for ADHD by altering the gut microbiota. Male spontaneously hypertensive rats (SHR) and Wistar Kyoto (WKY) rats were randomly allocated to the normal diet (ND), methylphenidate (MPH), and KD groups. SHR in groups KD and MPH exhibited a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Approximately 65–89% of adults with ADHD experience one or more comorbid psychiatric conditions, and ADHD often occurs comorbid with anxiety and depression ( 41 ). Preclinical studies in murine models ( 42 ) of ADHD with hyperactivity suggest that KD may improve symptoms via alteration of the gut microbiome. Preclinical studies in dogs with epilepsy displaying ADHD-like behaviors treated with a medium-chain triglyceride KD have shown decreased pathological behaviors ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 65–89% of adults with ADHD experience one or more comorbid psychiatric conditions, and ADHD often occurs comorbid with anxiety and depression ( 41 ). Preclinical studies in murine models ( 42 ) of ADHD with hyperactivity suggest that KD may improve symptoms via alteration of the gut microbiome. Preclinical studies in dogs with epilepsy displaying ADHD-like behaviors treated with a medium-chain triglyceride KD have shown decreased pathological behaviors ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of the amelioration of epilepsy by ketogenic diets seem to be multifaceted, involving both the gut-brain axis and microbiota 8 , and regional changes within the brain including accumulation of gamma-aminobutyric acid (GABA) and elevated GABA/glutamate ratio 1 . Interestingly, reduction in GABA was also observed in attention-deficit/hyperactivity disorder (ADHD), another neuronal disorder that could potentially be alleviated by ketogenic diets 9 . Recently, using similar analyses, we found that a high fat low carbohydrate food environment is also associated with reduced ADHD disease burden 10 .…”
mentioning
confidence: 99%